Health Risk Assessment Of Persistent Organic Pollutants Through Consumption Of Chicken Meat - Abdul Latiff, Zurinah (2008)
Persistent organic pollutants (POPs) are widely dispersed throughout the environment including food. Bahan-bahan pencemar organik persisten (POPs) di dapati tersebar dengan meluasnya di alam sekitar termasuk makanan.